A value chain analysis of antimony beneficiation opportunities for South Africa - Ndhlovu, Lucia Tsakani (My University, 2021)
Antimony is considered a critical and strategic commodity by the European Commission because its production is highly concentrated in China, and it is used in various applications. Antimony in South Africa was historically mined in the Limpopo Province from the early 1940s. Production ceased in 2014 after the antimony mine was placed under provisional liquidation. The mine was reported to have over 25 000t of underground antimony reserves and over 200 000t of antimony resources at the time (Village Main Reef, 2013). The antimony value chain is not prioritized in South Africa’s Mineral Beneficiation Strategy; however, antimony demand is likely to grow. This presents South Africa with an opportunity tore-enter the antimony market as a supplier of various antimony-based products. The report finds that if certain constraints are mitigated, the country has the potential to successfully re-enter the antimony market in the short–medium term
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2021